A visual 3D perception of the ski course and skiing results - Aleshin, V.; Klimenko, S.; Bobkov, A.; Novgorodtsev, D. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The importance of possessing the proper skills "to see the course" ("Toni" Sailer) is well known. In this study, an attempt to evaluate visual 3D perception different factors to the results of the virtual skiing is presented.